Motorcycle final drive geometry optimization on uneven roads - Alcázar-Vargas, Manuel Gonzalo; Pérez-Fernández, Javier; Mata-Bago, José Enrique; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (Elsevier, 2019)
The design of transmission systems plays an important role in the dynamic performance of motorcycles. It is well known that power delivery and stability in motorcycles is strongly affected by the geometry of the final drive. This article presents a 2D multibody motorcycle model in which the tire and final drive are considered thoroughly. A nonlinear transient model is used to reproduce forces between the tire and the road. The engine and wheel sprockets, the squat ratio and the chain slack have been taken into account in the final drive kinematic model. The configuration of the final drive elements and its influence on the distance covered by the motorcycle have been studied. Furthermore, the motorcycle final drive design has been optimized to maximize the distance traveled on different uneven roads. Simulations show a superior performance of the motorcycle when the configuration of the final drive elements is optimized. This study contributes to demonstrating the importance of the configuration and geometry of the final drive to improve stability and overall be- havior of the motorcycle on uneven roads.
Keywords: Motocicletas - Transmisión - Diseño; Motorcycle modeling; Final drive; Genetic algorithm optimization; Transient tire model